The version that wanted to be written Writing the Nazi past as historiographic metafiction (Volume 13) - Giblett, Kylie (2021)
The unification of Germany in 1990 set in train a number of dramatic changes in Germany's political, social and cultural landscape which gave rise to a series of hotly debated memory contests centred on the newly unified nation's approach to its common Nazi past. As an important medium of cultural memory, literature played a significant part in the controversy and novels dealing with the Nazi past enjoyed widespread popularity and influence in the 20 years following 1990. But what ""version"" of the Nazi past did the authors of these novels choose to tell? Using the perpetrator/victim dichotomy around which much of the debate crystallised, this book seeks to answer this question via a close textual analysis of works by Bernhard Schlink, Ulla Hahn, Tanja Dückers, and Marcel Beyer. In particular, this book analyses these novels as historiographic metafiction, a significantly under-explored angle which raises important questions concerning our ability to know the "truth" about the past and destabilises the basis on which we judge guilt or innocence. In providing a deeper understanding of the approach of fiction authors to the Nazi past in the post-1990 period, this book aims to enrich our understanding of its legacy in contemporary German society today.